Social Responsibility and Organisational Commitment in Local Public Administration: The Moderating Role of Organisational Citizenship Behaviour and Social Bonding - Kalsoom BeBe; Wang Bing (Central European Public Administration Review)
The commitment of public employees to organisations is an imperative deliberation that affects the efficiency of public services organisations. The objective of this study is to investigate whether the social responsibility among local public administrators raises organisational commitment. This study subsequently explores the moderating role of citizenship behaviour and social bonding (permanent vs temporary employees) of public employees in the relationship between social responsibility and organisational commitment. In this study, empirical data are collected from local officials working in local public administration services organisations in Pakistan (n = 308). The statistical analysis is used to test the relationship between social responsibility and commitment and the moderating effect of citizenship behaviour and social bonding on social responsibility-organisational commitment relationship. The results show that social responsibility is a determinant to organisational commitment and citizenship behaviour and social bonding moderate the social responsibility-commitment relationship. The effect of social responsibility on organisational commitment is stronger in permanent public administrators having high perspective of organisational citizenship behaviours than in temporary public administrators having low perspective of organisational citizenship behaviours. This study contributes to knowledge of the effect of social responsibility on organisational commitment in local public employees and proves that citizenship behaviour and social bonding affect the social responsibility-commitment relationship in local public administrators.